Daniel's story - Matas, Carol, 1949- (New York : Scholastic, 1993)
Daniel, whose family suffers as the Nazis rise to power in Germany, describes his imprisonment in a concentration camp and his eventual liberation.
"Published in conjunction with the United States Holocaust Memorial Museum"--Front cover.
720
Accelerated Reader AR
Keywords: Holocaust, Jewish (1939-1945) -- Fiction; Jews -- Persecutions -- Fiction